Development of Nitrate-Nitrogen Calibration Curve using Laboratory Resistivity Method at Neutral pH Condition - Hasshrin, Muhammad Safek; Wan Mohamed @ Wan Abd Ghani, Wan Afnizan (Recent Trends in Civil Engineering and Built Environment, 2024)
Nutrients come from a variety of different sources. Nutrient pollution occurred when the process of too many nutrients, mainly consist of nitrogen and phosphorus, added to waterbody and act like fertilizer causing algal blooms. In this study, a calibration curve between nitrate-nitrogen concentration and resistivity is developed. It was to determine the electrical resistivity value of nitrate-nitrogen concentration at neutral range which covers from pH 6.4 to pH 7.4 as well as determine its electrical resistivity value at high (200 mg/L to 1000 mg/L), medium (20 mg/L to 100 mg/L) and low (2 mg/L to 10 mg/L). The stock solution of Sodium Nitrate Stock that were prepared were adjusted its pH value with different molarity of balancing solution, which is base solution (NaOH) and strong acid solution (H2SO4). It then repeatedly conducted with various dilution concentration from low (2 mg/L to 10 mg/L), medium (20 mg/L to 100 mg/L), and high (200 mg/L to 1000 mg/L). Then, the solution was tested with soil box resistivity meter to obtained the resistance reading before tabulated and analyzed for the resistivity value. From both data obtained, the calibration curve was generated between nitrate-nitrogen and electrical resistivity value. From this study, it can be found that the trendline for most of the calibration curve generated were showing a polynomial trendline as the R2 reading illustrated closer to 1.000. At the end of this study, it concludes that value of electrical resistivity value is decreasing gradually as the concentration solution increased thus proving that there were ions presents in the solution